Delivering mRNA to Secondary Lymphoid Tissues by Phosphatidylserine‐Loaded Lipid Nanoparticles. Issue 9 (25th December 2022) - Gomi, Masaki; Sakurai, Yu; Sato, Minami; Tanaka, Hiroki; Miyatake, Yumi; Fujiwara, Koichi; Watanabe, Mizuki; Shuto, Satoshi; Nakai, Yuta; Tange, Kota; Hatakeyama, Hiroto; Akita, Hidetaka
Abstract: Lipid nanoparticles (LNPs) are one of the most successful technologies in messenger RNA (mRNA) delivery. While the liver is the most frequent target for LNP delivery of mRNA, technologies for delivering mRNA molecules to extrahepatic tissues are also important. Herein, it is reported on the development of an LNP that targets secondary lymphoid tissues. New types of alcohol‐soluble phosphatidylserine (PS) derivatives are designed as materials that target immune cells and then incorporated into LNPs using a microfluidic technique with a high degree of scalability and reproducibility. The resulting LNP that contained the synthesized PS delivered mRNA to the spleen much more efficiently compared to a control LNP. A sub‐organ analysis revealed that the PS‐loaded LNP is extensively taken up by tissue‐resident macrophages in the red pulp and the marginal zone of the spleen. Thus, the PS‐loaded LNP reported in this study will be a promising strategy for clinical applications that involve delivering mRNA to the spleen. Abstract : The alcohol‐soluble phosphatidylserine (PS) derivatives are synthesized and then loaded with lipid nanoparticles (LNP). The PS‐loaded LNPs efficiently accumulate in the spleen and deliver the messenger RNA cargo after intravenous injection. A sub‐organ analysis reveals that the PS‐loaded LNPs are extensively taken up by spleen‐resident macrophages localized in the red pulp and the marginal zone.